Mental Health Challenges among Financially Disadvantaged Students at South African Universities: A Scoping Review - Tiisetso Aubrey Chuene; Banele Nkosingiphile Siboza (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
Background: Financial constraints are a significant stressor for university students in South Africa, particularly those without stable financial support. These students often face challenges in meeting tuition, accommodation, and other basic needs, which may negatively impact their mental health. Despite growing recognition of student mental health, the experiences of financially disadvantaged students remain underexplored. Aims: This scoping review maps and synthesises evidence on mental health challenges among financially disadvantaged students at South African universities, identifying key stressors, associated factors, and research gaps Methods: A comprehensive search of peer-reviewed and grey literature was conducted across Google Scholar, PubMed, Sabinet, Psych-info, and Web of Science for studies published between January 2020 and December 2025. Eligible studies focused on financially disadvantaged students at South African universities and reported mental health outcomes. Two reviewers independently screened studies and extracted data, with disagreements resolved through consensus. The final search was completed on 31 January 2026. Sixteen studies were included and analysed using a narrative synthesis approach guided by a thematic approach. Results: Financially disadvantaged students consistently reported anxiety, stress, depressive symptoms, and psychological distress associated with financial hardship. The most represented populations were first-year students, low-income or rural students, and NSFAS-funded students. Food insecurity, unstable accommodation, and academic pressure commonly co-occurred with financial hardship, while limited access to mental health services further compounded these challenges. Few studies examined integrated interventions addressing both financial and mental health challenges. Conclusion: Financially disadvantaged students face complex mental health challenges driven by socio-economic and institutional factors. A major gap identified is the lack of integrated interventions addressing both financially disadvantaged students and mental health. The findings highlight an urgent need for coordinated context-specific institutional responses that integrate financial support, mental health services, and academic assistance within South African higher education.